The Effect of Trade Openness and Political Fragility on Foreign Direct Investment - Wardani, Dyah Titis Kusuma (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
This study examines the influence of trade openness and political fragility on Foreign Direct Investment (FDI) inflows in six ASEAN countries: Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam, over the period from 2013 to 2022. Trade openness is analyzed as a critical economic factor that can attract FDI by facilitating international trade and reducing barriers. Political fragility represents the political dimension, reflecting how instability and weak governance can deter foreign investors. Additional economic factors considered include market size, interest rates, and infrastructure, while crime rates represent the social dimension affecting investment decisions. Secondary data were sourced from the World Bank, Numbeo, and The Fund for Peace. Panel data regression analysis was conducted using Ordinary Least Squares (OLS), and the Common Effect Model was selected. The results reveal that trade openness has a positive and significant impact on FDI inflows, emphasizing the importance of liberal trade policies in attracting foreign investment. Conversely, political fragility negatively and significantly affects FDI, highlighting that political instability can undermine investor confidence. Market size and interest rates also positively influence FDI, while infrastructure and crime rates have a negative effect. These findings suggest that governments aiming to boost FDI should prioritize enhancing trade openness and addressing political fragility by fostering stable political environments and effective governance.